2012
DOI: 10.1007/s10792-011-9499-8
|View full text |Cite
|
Sign up to set email alerts
|

Candida dubliniensis endophthalmitis: first case in North America

Abstract: To report an unusual case of endogenous fungal endophthalmitis due to Candida dubliniensis. Interventional case report of a 27-year-old immunocompetent male with loss of vision, dense vitritis, and chorioretinal infiltrates, who underwent a diagnostic pars plana vitrectomy. Microbiology cultures obtained by a diagnostic vitrectomy were positive for the growth of C. dubliniensis. This infectious process was then appropriately treated with intravitreal amphotericin B and systemic fluconazole with resolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The case is indeed very rare, but it is important to mention that this should not be considered the first case report in North America [1]. The present case is a ''27-year-old immunocompetent male with loss of vision, dense vitritis, and chorioretinal infiltrates'' [1].…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The case is indeed very rare, but it is important to mention that this should not be considered the first case report in North America [1]. The present case is a ''27-year-old immunocompetent male with loss of vision, dense vitritis, and chorioretinal infiltrates'' [1].…”
mentioning
confidence: 74%
“…The present case is a ''27-year-old immunocompetent male with loss of vision, dense vitritis, and chorioretinal infiltrates'' [1]. There is no doubt that this rare infection should be kept in mind by the ophthalmologist.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…This case was initially thought to represent the first case of C. dubliniensis endophthlamitis in North America, but a letter to the editor sent by Wiwanitkit revealed that the first case was indeed the one discussed above, rendering the case by Espinosa-Heidmann et al second on the list [20]. This case concerned a 27-year-old white male with a history of intravenous drug use as his only risk factor, and onychomycosis as the suspected source of infection [16].…”
Section: Discussionmentioning
confidence: 96%
“…The first reports of fungemia from C. dubliniensis were in patients with leukemia, HIV, or end-stage liver disease. The most common risk factors are intravenous drug abuse, HIV infection, bone marrow and solid organ transplantation, and neutropenia resulting from chemotherapy [16,17]. It is also a reported cause of catheter-related fungemia.…”
Section: Discussionmentioning
confidence: 99%